Comparison of ALitretinoin with PUVA as the first-line treatment in patients with severe chronic HAnd eczema (ALPHA): study protocol for a randomised controlled trial. Issue 2 (23rd February 2022) - Smith, Isabelle L; Gilberts, Rachael; Brown, Sarah; Fernandez, Catherine; Nixon, Jane; Reynolds, Catherine; Smith, Catherine; Lear, John T; Sunderland, Lesley; Green, Cathy; Goodfield, Mark; Cowdell, Fiona; et al.
Abstract : Introduction: Hand eczema (HE) is one of the most common skin disorders and an important cause for morbidity and occupational disability. The 1-year prevalence of HE is estimated to be up to 10% and it is estimated that 5%–7% of those develop severe chronic HE. However, current clinical evidence is not compelling enough to guide clinical practice. In a survey among 194 UK dermatologists the most frequent first choice approaches were psoralen combined with ultraviolet A (UVA) treatment (PUVA), oral steroids and alitretinoin (AL). When asked which strategy was most efficient for long-term outcome 20% of clinicians indicated they did not know; 43% of clinicians reported AL and 30% reported PUVA. Methods and analysis: ALPHA is a multicentre, open, prospective, two-arm parallel group, randomised controlled trial comparing PUVA and AL with a planned sample size re-estimation. Between 500 and 780 participants will be randomised on a 1:1 basis. The physician's global assessment (PGA) will direct treatment after randomisation, non-responders will be treated according to usual clinical practice; providing valuable pilot data on second line therapeutic approaches to inform future trials. Assessments will be conducted up to 52 weeks post randomisation. The primary outcome measure is the Hand Eczema Severity Index at 12 weeks. Secondary outcome measures include modified Total Lesion Symptom Score, PGA, time to relapse, patient reported outcome measures and DNA extraction and assessment of genetic variants. A substudy on molecular inflammatory mediators will provide information on subgroup specific treatment responses. Photographs will be taken and HE severity assessed by a central review panel. Ethics and dissemination: Ethics approval was obtained from Leeds West Research Ethics Committee (14/YH/1259).Trial results will be disseminated at relevant clinical conferences and societies, published in peer-reviewed journals and through relevant patient groups. Trial registration number: ISRCTN80206075 .